Citizen journalism as a contestant in the history of journalism. Issue 1 (2nd January 2017) - Mapudzi, Hatikanganwi; Osunkunle, Oluyinka
ABSTRACT: This article looks at citizen journalism as a contestant in the history of journalism. It reports on a study that employed a qualitative research approach through a qualitative questionnaire and a focus group discussion (FGD). Through purposive sampling, the participants in the study were drawn from the citizen journalists contributing news content to the citizen journalism websites Sahara Reporters and Iindaba Ziyafika from a Nigerian and a South African perspective, respectively. For diversity purposes, other participants were drawn from the Global Voices online, which is popular for engaging citizen journalists from different parts of the African continent: Tanzania, Cameroon, Ghana, Mozambique and Kenya, to mention a few. The questionnaire was distributed through the technical teams of the websites for self-completion by the citizen journalists. The FGD participants were drawn from those who contributed news content to Iindaba Ziyafika in South Africa where the researchers are based. The questionnaire and the FGD were addressed in English. The study findings showed that mainstream journalism acknowledges the importance of the phenomenon of citizen journalism and the people involved, but it still stands firm that objectivity is a precondition of journalism. The study aimed to cultivate an appreciation of the relationship between traditional and citizen journalism as the field of journalism endures major transformations.